2015
DOI: 10.1097/md.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Spinal Neurilemmoma

Abstract: Neurilemmoma commonly occurs from the fourth to sixth decades of life with an incidence of 3 to 10 per 100,000 people, and is rare in adolescence. This case report describes the clinical and radiographic features of 2 rare cases with intraspinal neurilemmoma of the cervical and thoracic spine.A 29-year-old man who experienced middle back pain with prominent right lower limb weakness, and an 11-year-old boy who suffered from sudden onset neck pain with left arm weakness and hand clawing for 2 weeks before admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…4 Yeh et al have published an 11-year-old boy with schwannoma of the C 6-7 that was presented with forearm pain and progressive weakness and clawing hand. 11 Mohanty et al reported another schwannoma of the neck in a 10-year-old boy, presented also with swelling in the neck and symptoms from swallowing and voice hoarseness that was arising from C 4 body and with destruction of the vertebral body. 12 Landi et al described the case of a 8-year-old female affected by a progressive paraparesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Yeh et al have published an 11-year-old boy with schwannoma of the C 6-7 that was presented with forearm pain and progressive weakness and clawing hand. 11 Mohanty et al reported another schwannoma of the neck in a 10-year-old boy, presented also with swelling in the neck and symptoms from swallowing and voice hoarseness that was arising from C 4 body and with destruction of the vertebral body. 12 Landi et al described the case of a 8-year-old female affected by a progressive paraparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pokharel et al report an extradural cervical spinal schwannoma, in a 14‐year‐old child, that was presented with a single swelling of the posterior triangle of the neck with normal muscle strength and absence of sensory deficit 4 . Yeh et al have published an 11‐year‐old boy with schwannoma of the C 6‐7 that was presented with forearm pain and progressive weakness and clawing hand 11 . Mohanty et al reported another schwannoma of the neck in a 10‐year‐old boy, presented also with swelling in the neck and symptoms from swallowing and voice hoarseness that was arising from C 4 body and with destruction of the vertebral body 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In the article “Surgical Outcome of Spinal Neurilemmoma: Two Case Reports”, 1 which appeared in Volume 94, Issue 5 of Medicine , Dr. Kuang-Ting Yeh's credentials were incorrectly listed as MD, PhD. Dr. Yeh is an MD and not a PhD.…”
mentioning
confidence: 99%